Pengembangan dan Pengujian Sistem Grid Computing Menggunakan Globus Toolkit di Universitas Telkom - Izzatul Ummah (School of Computing, Telkom University, 2017)
In this research, we build a grid computing infrastructure by utilizing existing cluster in Telkom University as back-end resources. We used middleware Globus Toolkit 6.0 and Condor 8.4.2 in developing the grid system. We tested the performance of our grid system using parallel matrix multiplication. The result showed that our grid system has achieved good performance. With the implementation of this grid system, we believe that access to high performance computing resources will become easier and the Quality of Service will also be improved.